In vitro digestion of foods using pH-stat and the INFOGEST protocol: Impact of matrix structure on digestion kinetics of macronutrients, proteins and lipids. (October 2016) - Mat, Damien J.L.; Le Feunteun, Steven; Michon, Camille; Souchon, Isabelle
Abstract: It is currently admitted that food structure can facilitate or delay the release of nutrients during digestion and their absorption by the human body. The aim of this study is to propose an in vitro method able to assess the behavior of lipo-proteinic matrices with different structures during digestion. Two model matrices of exactly the same compositions (10% oil, 15% whey proteins, w / w ) were designed: i) A liquid emulsion (LE) made of small fat droplets (1 μm) dispersed in a liquid continuous phase containing native whey proteins, ii) a solid emulsion (SE) made of a continuous whey protein gel entrapping large oil droplets (20 μm). The two matrices were digested through an in vitro gastro-intestinal protocol based on the INFOGEST guidelines using pH-stat to monitor the enzymatic hydrolyses of both proteins and lipids. By further digesting lipid-free matrices in the same conditions, the contributions of the proteolytic and lipolytic reactions were evaluated. Significant differences were observed between matrices at both short and long digestion times. The initial rates of both proteolysis and lipolysis were slower for SE than LE because of the gel state of the continuous phase. At the end of the experiments, SE led to a smaller extent of lipolysis (DHlip_SE  = 51% < DHlip_LE  = 81%) but a greater extent of proteolysis (DHprot_SE  = 80% > DHprot_LE  = 52%) because of the higher sensitivity to digestion of denatured whey proteins. These results highlight the impact of matrix structure on enzyme accessibility, and show that the proposed method is suitable to monitor the digestion of complex food matrices. Highlights: Proteinic emulsions of identical composition but different structures were designed. The INFOGEST in vitro digestion protocol was adapted to allow pH-stat measurements. The intestinal hydrolysis kinetics of both proteins and lipids were monitored. Matrix structure strongly influenced both the protein and lipid digestion kinetics. The final extents of lipid and protein digestion (DH) were also different.